Brand-to-Generic Substitution of Buprenorphine/Naloxone Sublingual Film in Puerto Rico: A Case Study - Santiago, Darlene; Rosario, Yarelis; Melin, Kyle; Duconge, Jorge; Roman, Luis; Gonzalez, Angel; Venkataramanan, Raman (Puerto Rico Health Sciences Journal, 2021)
A 56-year-old patient with a 1-year history of stable maintenance treatment with Suboxone for opioid use disorder (OUD) was switched to a generic formulation in May of 2019. The patient reported experiencing—over the course of the following 3 months—withdrawal symptoms when switched to the Alvogen-produced generic formulation in May of 2019 and then to the Sandoz-produced version in July of that same year, she also was positive for fentanyl during that time. As a result, the buprenorphine dose was increased, and the patient was stable at this new dose using the generic versions. Blood levels pre- and post-change (not reported in previous case reports) showed maximum buprenorphine concentration being reached more quickly when the brand-name drug was used. Additionally, the area under the curve (AUC) values indicate that the generic formulation had higher exposures than the brand-name drug. Based on the clinical impact of the brand-to generic switch in this patient, further research in this area is warranted. In the meantime, clinicians should carefully monitor their patients so that, if warranted, dose adjustments can be made quickly and safely to minimize negatively impacting the OUD therapy outcomes of patients.